Structural and Thermo-Mechanical Properties of Poly(ε-Caprolactone) Modified by Various Peroxide Initiators - Przybysz, Marta (Polymers (Basel), 2019)
The modification of poly(ε-caprolactone) (PCL) was successfully conducted during reactive processing in the presence of dicumyl peroxide (DCP) or di-(2-tert-butyl-peroxyisopropyl)-benzene (BIB). The peroxide initiators were applied in the various amounts of 0.5 or 1.0 pbw (part by weight) into the PCL matrix. The effects of the initiator type and its concentration on the structure and mechanical and thermal properties of PCL were investigated. To achieve a detailed and proper explication of this phenomenon, the decomposition and melting temperatures of DCP and BIB initiators were measured by differential scanning calorimetry. The conjecture of the branching or cross-linking of PCL structure via used peroxides was studied by gel fraction content measurement. Modification in the presence of BIB in PCL was found to effectively increase gel fraction. The result showed that the cross-linking of PCL started at a low content of BIB, while PCL modified by high DCP content was only partially cross-linked or branched. PCL branching and cross-linking were found to have a significant impact on the mechanical properties of PCL. However, the effect of used initiators on poly(ε-caprolactone) properties strongly depended on their structure and content. The obtained results indicated that, for the modification towards cross-linking/branching of PCL structure by using organic peroxides, the best mechanical properties were achieved for PCL modified by 0.5 pbw BIB or 1.0 pbw DCP, while the PCL modified by 1.0 pbw BIB possessed poor mechanical properties, as it was related to over cross-linking.